Convergence Insufficiency Neuro-mechanism in Adult Population Study Randomized Clinical Trial: Clinical Outcome Results. Issue 12 (December 2020) - Alvarez, Tara L.; Scheiman, Mitchell; Santos, Elio M.; Yaramothu, Chang; d'Antonio-Bertagnolli, John Vito
Abstract : SIGNIFICANCE: These data confirm the effectiveness of office-based vergence/accommodative therapy for improving the near point of convergence and positive fusional vergence in young adults with symptomatic convergence insufficiency within a double-masked longitudinal randomized clinical trial. PURPOSE: This study aimed to report changes in clinical signs and symptoms of convergence insufficiency from a randomized clinical trial evaluating the effectiveness of office-based vergence/accommodative therapy for young adults with symptomatic convergence insufficiency. METHODS: In this double-masked, randomized clinical trial, convergence insufficiency patients (n = 50; average age, 21 ± 3 years; range, 18 to 32 years) were randomized to either office-based vergence/accommodative therapy or office-based placebo therapy. Improvements in (1) near point of convergence, (2) positive fusional vergence, and (3) self-reported symptoms (Convergence Insufficiency Symptom Survey [CISS] score) were evaluated after twelve 1-hour sessions of treatment within the office comparing the results from the vergence/accommodative therapy and the placebo therapy groups. RESULTS: The mean near point of convergence improved by 6.0 and 3.1 cm in the vergence/accommodative and placebo therapy groups, respectively (mean difference of −2.9 cm; 95% confidence interval [CI], −4.6 to −1.0 cm; P < .01). The mean positive fusional vergence increased by 17.3 and 7.4Δ in the vergence/accommodative and placebo therapy groups, respectively (mean difference of 9.9Δ; 95% CI, 4.9 to 16.0Δ; P < .001). The mean CISS score improved by 12.4 and 10.1 points in the vergence/accommodative and placebo therapy groups, respectively (mean difference of 2.3 points; 95% CI, −8.3 to +4.6 points; P = .56). CONCLUSIONS: Our results demonstrate that office-based vergence/accommodative therapy is effective for improving the near point of convergence and positive fusional vergence in young adults with symptomatic convergence insufficiency. However, given that both treatment groups had a similar reduction in self-reported symptoms, we recommend that the CISS be revised if it is to be used as an outcome measure in future studies of convergence insufficiency.